Murach's HTML5 and CSS3 - Boehm, Anne (Shroff, 2019)
"Until now, my websites looked great but have been coded with what seems like 'duct-tape and bubble-gum' methods, just for appearances and not for professionalism or compliance. This book taught me all that is possible with HTML and CSS coding]]. What a game changer!"